Mapping Community Land in North Sumatra through the Implementation of Agrarian Reform - Onny Medaline; Fitri Rafianti; Rahmad Sembiring (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Agrarian Reform is an operation to reorganize agrarian structures that experience inequality to create a new, more just structure. The President as the highest leader of the state is a mandatory implementer of agrarian reform to systematically through his authority carry out conflict resolution and overhaul the structure of agrarian inequality. This is directly stated in the constitution of our country, the 1945 Constitution, and the Basic Agrarian Law no. 5 of 1960. This mandate was strengthened through MPR Decree No. IX of 2001 concerning Agrarian Reform and Natural Resources. Presidential Regulation Number 86 of 2018 concerning Agrarian Reform emphasizes asset management, access arrangement, and land dispute resolution. The agrarian reform movement is concerned, that the agenda for implementing agrarian reform will be neglected, there will be more lip service and ceremonial without touching the root of the real agrarian problem, even in the form of a political promise by the government to the community. And it has great potential to further deviate from the accuracy of the objects and subjects of Agrarian Reform that are not my main purpose. The Presidential Regulation on Agrarian Reform Number 86 of 2018 is considered a political breakthrough. It is strongly suspected that the suitability of the object (land) and the subject (recipient) of land redistribution is wrong and does not match the objectives of agrarian reform. Including the absence of supporting programs after the redistribution is carried out, as a condition of Agrarian Reform.